A Terminally Capped Synthetic, Acyclic Tripeptide Forms Dimer in the Solid, Liquid and Gaseous States. Issue 9 (2nd March 2018) - Samui, Satyabrata; Chakraborty, Arpita; Biswas, Soumi; Singh, Gajendra; Mondal, Swastik; Ghosh, Semanti; Bagchi, Angshuman; Ampapathi, Ravi S.; Naskar, Jishu
Abstract: Boc‐Ala‐Leu‐Tyr‐OMe (Boc: tert‐butyloxycarbonyl, Me: methyl), an acyclic, terminally capped tripeptide forms dimer in the solid, liquid and gaseous states. In the solid state, the dimer structure has been confirmed by single crystal X‐ray diffraction study. From the analysis of diffraction data, it is revealed that two independent peptide molecules, in the antiparallel β‐sheet arrangement, are present in the asymmetric unit and are stabilized by three intermolecular hydrogen bonds. In the liquid phase, the structure has been established from nuclear magnetic resonance (NMR) spectroscopy. The Δδ/Δ T values obtained from temperature dependent NMR studies are in good agreement with the antiparallel dimer structure in solution. Further, the rotating frame overhauser effect spectroscopic (ROESY) study also supports the antiparallel staking of the peptide in solution. The existence of dimer in the gas phase has been proved by electrospray ionisation mass spectrometric (ESI‐MS) study. The m/z values of the ESI‐MS spectrum support the formation of dimer at the gaseous condition. Molecular mechanics simulation study also corroborates the results. This is the first report of the robust peptide‐dimer that exists in all the three physical states and facilitates the understanding of intermolecular β‐sheet interactions in various complex biological systems. Abstract : Boc‐Ala‐Leu‐Tyr‐OMe, an acyclic, terminally capped tripeptide forms dimer in the solid, liquid and gaseous states. Single crystal X‐ray diffraction study, NMR and ESI‐MS confirm the dimer structure in the solid, liquid and gaseous states respectively. Molecular mechanics simulation study also corroborates the results. This is the first report of the robust peptide‐dimer that exists in all the three physical states and facilitates the understanding of intermolecular β‐sheet interactions in various complex biological systems.